Ընդհանուր ակնարկ` հայագիտութեան մէջ «գիտականը» - Չիլինկիրեան Հրաչ / Tchilingirian Hratch (Հայաստանի ազգային գրադարան / National Library of Armenia, 2025)
This article addresses the enduring issue of scientific standards and methodological approaches in various fields of study, with a particular focus on contemporary Armenian studies. It examines the necessity of adopting internationally recognized scientific standards and methodologies in the humanities and social sciences in Armenia to ensure the global competitiveness of Armenian research. The discussion emphasizes the distinction between personal opinions and rigorous scientific analysis, advocating for the consistent application of scholarly principles. The article also highlights the importance of integrating Armenian studies into the global scientific community. It concludes by urging Armenian researchers to adopt high-quality research methodologies and international standards to enhance the global recognition and impact of Armenian scholarship.
Հայ բանասիրութեան հեռանկարներ։ Ուսումնասիրութեան եւ ուսուցման արդի խնդիրներ / Պատ. խմբ. եւ կազմող՝ Ն. Պօղոսեան ; Խմբ. խորհուրդ՝ Տ. Յովնան Արք. Տէրտէրեան եւ այլք .- Երեւան ; Լոս Անջելէս. ։ ԱՄՆ Արեւմտեան թեմի Առաջնորդարան ; «Գիրք» հրատարակչություն , 2025 .- էջ 238-241։
Keywords: Հայագիտություն